Attachment and Affect Regulation Theories and the Existential/Developmental Model (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
This is a theoretical paper integrating attachment and affect regulation theories with an existential-developmental model that was first presented in 2002 at the Third World Congress for Psychotherapy held in Vienna. At that time, a variety of developmental theories (Erikson, Freud, Piaget, Bowlby, Mahler and Winnicott) were combined in order to describe development as a spiral from birth to death. The term 'DNA of the soul' was used, with the intertwining double helix symbolizing the ongoing dynamic interaction of positive (growth enhancing) and negative (growth inhibiting) possibilities which, at each stage of development, forge our evolutionary path through life. New neurobiological advancements are giving light and support to the existence of this 'psychological DNA' that becomes part of our thrownness in life. It constitutes our psychological inheritance that, in contradistinction to our biological DNA, can be changed with courage and will power.
Keywords: Attachment; affect regulation; freedom; thrownness; existential-developmental